Strategi Efektif Pengembangan Pariwisata Pantai Mutun Sebagai Wisata Bahari di Kabupaten Pesawaran Provinsi Lampung - Muhamad Derry Andian; Neli Aida (Journal on Education, 2023)
Mutun Beach is a tourist attraction in Pesawaran Regency, which has the advantage of being marine tourism. This study aimed to determine how the tourism development strategy at Mutun Beach is expected to increase tourist attraction and local revenue. This study uses a SWOT analysis tool consisting of 4 stages: identifying internal and external factors, creating a SWOT Matrix, analyzing the IFAS Matrix and EFAS Matrix, and creating a SWOT Quadrant. Fifteen selected expert respondents filled out this questionnaire. The results of this study indicate that the strategy for developing Mutun Beach tourism is 1) Marketing Mutun Beach tourism on platforms, websites, and other social media so that it can develop quickly and be known by many tourists, as well as maximize existing facilities and infrastructure. 2) Recruiting human resources who are competent in their fields and optimizing existing infrastructure facilities so that they are maintained and maintained in the future. 3) Improving cleanliness and maintaining tourist attractions such as tourist attractions so that they still look beautiful and memorable for tourists to come back. 4) Tighten supervision of tourists who swim by involving residents who understand the surrounding conditions.